Eksplorasi Penderitaan (Suffering) Pada Pasien Hemodialisis di Rumah Sakit Tentara Reksodiwiryo Padang - Inka Selvia; Emil Huriani; Fitri Mailani (Jurnal Ners, 2026)
Background: Patients undergoing hemodialysis face chronic illness and repeated therapy. This condition can cause patients to experience suffering that affects their health status, reduces their quality of life, increases rehospitalization, and leads to death. Objective: This study aims to explore the suffering of end-stage renal disease patients undergoing hemodialysis. Methods: Qualitative research was conducted using a descriptive phenomenological approach. Participants were selected using purposive sampling of 10 participants, and data were collected through semi-structured interviews. The study was conducted at the Reksodiwiryo Army Hospital in Padang. The interview guide was developed based on A Comprehensive Clinical Model of Suffering (CCMS). Data were analyzed using thematic analysis. Results: Four main themes were identified: (1) Physical suffering, (2) Psychological suffering, (3) Social suffering, and (4) Spiritual suffering. Conclusion: The results showed that suffering in hemodialysis patients is multidimensional and interrelated between physical, psychological, social, and spiritual aspects. Therefore, clinical services need to conduct multidimensional screening and develop individualized care plans that are responsive to the needs of each patient.